METHODOLOGICAL ISSUES OF ORGANIZING ACCOUNTING OF BIOLOGICAL ASSETS (World Economics and Finance Bulletin, 2025)
The article examines methodological issues of organizing the accounting of biological assets. The scientific research of foreign and domestic economists dealing with the issues of accounting of biological assets is studied. Accounts aimed at improving the organization of synthetic and analytical accounting of biological assets are proposed. A sample of primary accounting documentation is developed to improve primary accounting.